APLIKASI MONITORING MANAJEMEN OPERASIONAL PERKEBUNAN SAWIT BERBASIS WEB - Nur Laila; Ahmad Akbar; Chairul Rizal (Jurnal Nasional Teknologi Komputer, 2025)
The oil palm plantation sector in Indonesia faces significant operational efficiency challenges due to manual record-keeping, limited field activity monitoring, and suboptimal resource management, potentially leading to decreased yields and productivity. This research aims to develop a "Web-Based Oil Palm Plantation Operational Management Monitoring Application" for the AM4 Oil Palm Plantation in Alur Meranti Hamlet, Besitang District. The system is designed to provide accurate digital data recording and reporting, integrated with real-time field activity monitoring (including fertilization and maintenance), and integrated resource management. Utilizing the waterfall methodology, system development involved in- depth requirements analysis, design, implementation, testing, and maintenance. The results indicate that this application significantly enhances operational efficiency, data accuracy, and supports more effective managerial decision-making based on real-time data, surpassing the focus of previous research. This success demonstrates the substantial potential of information technology in optimizing oil palm plantation management, contributing to increased productivity and operational sustainability. Furthermore, the implementation of this web-based system is expected to minimize human error in data entry, provide a centralized database for easier access and analysis, and foster a more proactive approach to plantation management. By enabling real-time insights into crucial operational aspects, the application empowers plantation managers to make timely adjustments, optimize resource allocation, and ultimately boost overall output. This innovation serves as a model for other plantations grappling with similar challenges, highlighting the transformative power of digital solutions in modern agriculture.